2018
DOI: 10.1111/vco.12386
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint molecule expression by B and T cell lymphomas in dogs

Abstract: Immunotherapies targeting checkpoint molecule programmed cell death 1 (PD-1) protein were shown to be effective for treatment of non-Hodgkin lymphoma in people, but little is known about the expression of PD-1 or its ligand PD-L1 by canine lymphoma. Therefore, flow cytometry was used to analyse expression of PD-1 and PD-L1 in canine lymphoma, using fine-needle aspirates of lymph nodes from 34 dogs with B cell lymphoma (BCL), 6 dogs with T cell lymphoma (TCL) and 11 dogs that had relapsed. Furthermore, fine-nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…There have also been some reports on the PD-1/PD-L1 axis in dogs with different malignancies [ 13 , 14 , 33 ]. Recently, high expression of PD-1 on tumor infiltrating T cells was reported in dogs with B and T cell lymphoma [ 34 ]. In this study, significantly higher expression of PD-1 was observed on CD4+ T cells obtained from LNCs from dogs with lymphoma, and CD8+ T cells tended to up-regulate these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been some reports on the PD-1/PD-L1 axis in dogs with different malignancies [ 13 , 14 , 33 ]. Recently, high expression of PD-1 on tumor infiltrating T cells was reported in dogs with B and T cell lymphoma [ 34 ]. In this study, significantly higher expression of PD-1 was observed on CD4+ T cells obtained from LNCs from dogs with lymphoma, and CD8+ T cells tended to up-regulate these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Isotype‐matched, irrelevant antibodies were used at the same concentrations. To identify lymphocyte populations, B cell were identified as CD21 + (APC, clone CA2.1D6) and T cells were identified as CD5 + (FITC, clone YKIX322.3) from Bio‐Rad Laboratories (Hercules, California), as described previously …”
Section: Methodsmentioning
confidence: 99%
“…There are multiple reports of the expression of immune checkpoints in InvUC and other cancers in dogs (148)(149)(150)(151)(152)(153)(154)(155)(156)(157). In addition to the well-known checkpoints PD-1, PD-L1, CTLA-4, other checkpoints have been identified in canine InvUC (59, 157).…”
Section: Growing Role For the Dog Model To Drive Advances In Emergingmentioning
confidence: 99%